The Practical Encyclopedia of Pregnancy, Babycare & Nutrition for Babies & Toddlers - Mackonochie, Alison and Lewis, Sara (New York Lorenz Books, 2007)
This is a one-stop reference guide that will be essential reading from the moment you discover that you are pregnant covering everything you need to know about your pregnancy and new baby. The book is helpfully divided into four sections.
Include index and Colored Illustrations
Keywords: Pregnancy